(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
Tourism plays an important role in improving community welfare, with accommodation as the main facility for tourists to rest. This study analyzes the influence of individual personality on employee performance, with teamwork as a mediating variable. This study was conducted at Bali Silent Retreat, Tabanan, using a census method on 57 employees. Hypothesis testing using path analysis shows that teamwork partially mediates the relationship between individual personality and employee performance. Based on the results of the study, it is recommended to provide employee development training, provide brainstorming forums, implement a structured reporting system, hold regular meetings between divisions, and organize team-building to improve teamwork effectiveness.